(3EOGQI GdGfJGL aj GdefTBJ GdNOejI h GdUfGYjI (B:s (3eONd JMdjdj (B/s - (3Hf YfJQ, YHO GdQMefs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3EOGQI GdGfJGL(B- (3GdJWhQ GdJGQjNj dEOGQI GdGfJGL(B- (3CKQ JNWjW hJfXje GdYedjGJ GdGfJGLjIYdi GdcaGAI GdGfJGLjI(B- (3CKQ GdQbGHI hGdHQfGeL GdGfJGLj Ydi GdYedjGJ GdEfJGLjI aj JMbjb GdcaGAI GdGfJGLjI(B- (3GdGWGQ GdfXQj ddGfJGLjI hSHd hWQb JMSjfgG(B.s
(3eQGLY U(B.251s
Keywords: (3EOGQI GdGfJGLs; (3GdNOeGJs; (3GdUfGYIs